1991
DOI: 10.1159/000125730
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles for the Pituitary and Adrenal Cortex in the Control of Enkephalin Peptide Localization and Cortico-Medullary Interaction in the Sheep Adrenal during Development

Abstract: We have investigated the effect of adrenocorticotrophic hormone (ACTH) replacement after fetal hypophysectomy on the pattern of localization of enkephalin-containing peptides (enkephalins) and phenylethanolamine N-methyltransferase (PNMT) in the fetal sheep adrenal. We have also investigated the relative roles of the fetal pituitary and adrenal cortex in determining the extent of the interdigitation of the peripheral adrenaline (AD)-containing cells of the adrenal medulla with the inner zones of the adrenal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…development of the adrenal gland in the sheep fetus at late gestation. In agreement with previous studies, our data clearly demonstrate that the increase in adrenocortical growth and the prepartum increase in fetal plasma cortisol concentrations are dependent upon the presence of an intact fetal pituitary in the sheep fetus in late gestation (Basset & Thorburn, 1969;Boshier, Holloway & Liggins, 1981 ;Robinson et al 1983;Mesiano et al 1987;Coulter, Young, Browne & McMillen, 1991). In the present study, ACTH infusion (at 250 pg/ 24 h for 72 h ) in the hypophysectomized fetal sheep stimulated an increase in the adrenal weight, adrenal protein and fetal plasma cortisol concentrations beyond the normal levels found in the intact fetus at this gestational age.…”
Section: Molecular Weight Profile Of Enk-containing Peptides In Fetalsupporting
confidence: 92%
See 1 more Smart Citation
“…development of the adrenal gland in the sheep fetus at late gestation. In agreement with previous studies, our data clearly demonstrate that the increase in adrenocortical growth and the prepartum increase in fetal plasma cortisol concentrations are dependent upon the presence of an intact fetal pituitary in the sheep fetus in late gestation (Basset & Thorburn, 1969;Boshier, Holloway & Liggins, 1981 ;Robinson et al 1983;Mesiano et al 1987;Coulter, Young, Browne & McMillen, 1991). In the present study, ACTH infusion (at 250 pg/ 24 h for 72 h ) in the hypophysectomized fetal sheep stimulated an increase in the adrenal weight, adrenal protein and fetal plasma cortisol concentrations beyond the normal levels found in the intact fetus at this gestational age.…”
Section: Molecular Weight Profile Of Enk-containing Peptides In Fetalsupporting
confidence: 92%
“…In the present study, ACTH infusion (at 250 pg/ 24 h for 72 h ) in the hypophysectomized fetal sheep stimulated an increase in the adrenal weight, adrenal protein and fetal plasma cortisol concentrations beyond the normal levels found in the intact fetus at this gestational age. We observed previously that the adrenocortical area of hypophysectomized fetuses with ACTH replacement at 141-142 days of gestation was the same as that in intact fetal sheep at 145-147 days of gestation (Coulter et al 1991) and these data suggest that the level of ACTH replacement in the hypophysectomized group has accelerated the normal pattern of growth of the prepartum adrenal gland.…”
Section: Molecular Weight Profile Of Enk-containing Peptides In Fetalsupporting
confidence: 61%
“…Our results suggest that ACTH is the major regulator of these effects, since ACTH injections within 7 days restored plasma corticosterone level to control values. These results are in agreement with studies in the hypophysectomized fetal sheep, which showed that adrenal growth could be restored by in utero ACTH replacement therapy (6,8,24).…”
Section: Discussionsupporting
confidence: 92%
“…Glucocorticoid hormones are thought to exert negative feedback inhibition on hypothalamic-pituitary-adrenocortical axis activity at the pituitary, hypothalamic, and extrahypothalamic levels. This ultimately results in decreased synthesis and secretion of both corticotropin-releasing hormone (CRH) and other corticotropic secretagogues and in an inhibition of the production and secretion of ACTH (8,24). A rapid atrophy of the adrenal cortex and the reduction of its steroid machinery ensue.…”
mentioning
confidence: 99%
“…Although similar studies in the fetus have been more difficult, a role for ACTH in fetal adrenal development is indicated (6,7). Recent studies in the hypophysectomized fetal sheep have shown that adrenal cortical growth could be restored by in utero ACTH replacement therapy (8).…”
Section: Introductionmentioning
confidence: 99%